"Ausländer" (Foreigners), Migrants, or New Germans? Identity‐Building Processes and School Socialization Among Adolescents From Immigrant Backgrounds in Germany. Issue 160 (6th April 2018) - Schneider, Jens
Abstract: In public discourse in Germany, identity is widely constructed along the juxtaposition of two categories: "German"—defined primordially in ethnic terms—and "migrant" or "of migration background." But most urban schools today consist of a majority of children with such "non‐German" backgrounds, while "ethnic German" children have become one minority among many others. Drawing from research on German identity, social mobility careers from among second‐generation Turkey‐originating families—including retrospective accounts of their school experiences in the 1960s to 2000s—and a very recent project on urban diversity, this article compares experiences of native‐born adolescents and adults from immigrant families in relation to representations of Germanness. With immigrant children attending German schools over almost 50 years, it considers how demographic changes are shaping different experiences in the second and third generations and how this challenges German national self‐definitions. The discussion examines meanings and effects on identity building and future orientations of youth from immigrant families and implications for future research in "majority‐minority" societies.